Aldosterone Impaired Vascular Smooth Cell Function: from Clinical to Bench. (June 2015) - Chang, Yi-Yao; Chen, Ying-Hsien; Chou, Chia-Hung; Hung, Chi-Sheng; Tzeng, Yu-Lin; Wu, Xue-Ming; Wu, Vin-Cent; Ho, Yi-Lwun; Wu, Kwan-Dun; Lin, Yen-Hung
Abstract : Background/aim: Primary aldosteronism (PA) patients are correlated to higher cardiovascular events, endothelial function, and altered cardiac structure. However, theeffect of aldosterone on smooth muscle cell function is still unclear. One method to measure smooth muscle cell function is endothelial-independent vascular dilation. The key factor of endothelial-independent vascular dilation is sarcoplasmic reticulum ATPase (SERCA) level. Methods: We prospectively analyzed 35 patients with PA, and 30 patients with essential hypertension (EH) were enrolled as the control group. Flow and nitrate-mediated dilation (F/NMD) were performed in both groups and one year after operation in the patients with aldosterone producing adenoma (APA). Besides, we investigated the effect of aldosterone on SERCA regulation in vascular smooth muscle cell (VSMC) (T/G HA-VSMC). Results: PA patients had significantly lower FMD and NMD values than patients with EH (FMD: 13 ± 6 vs. 16 ± 4; NMD: 16 ± 6 vs.19 ± 5; both p  < 0.05). In correlation study, FMD/GMD were significant correlated with log 24 hour-urine aldosterone (FMD: r = −0.287, p  = 0.048; NMD: r = −0.402, p  = 0.005) but not blood pressure. Nineteen of APA patients received follow-up studyafter adrenalectomy. The impaired FMD/ NMD significantly resorted one year after adrenalectomy (FMD: 11 ± 4 to 19 ± 7; NMD: 15 ± 6 to 21 ± 6; both p  < 0.01). Under confocal microscopy, aldosteronesuppressed the expression of SERCA2aof VSMC. In q-PCR, aldosterone significantly suppressed the expression of SERCA2a mRNA since 10 −8  M. The process is through mitochondrial transcription factors A and B2. In western blot study, aldosteronealso significantly suppressed the expression of SERCA2a since 10 −8  M. Conclusions: Not only endothelial function, aldosterone also impaired smooth muscle cell function. SERCA 2a might play a role on aldosterone-induced smooth cell dysfunction.